Engaging fathers to improve complementary feeding is acceptable and feasible in the Lake Zone, Tanzania. (9th July 2021) - Martin, Stephanie L.; Matare, Cynthia R.; Kayanda, Rosemary A.; Owoputi, Ibukun; Kazoba, Aidan; Bezner Kerr, Rachel; Nnally, Luitfrid; Khan, Maliha; Locklear, Kamryn H.; Dearden, Kirk A.; Dickin, Katherine L.
Abstract: In Tanzania, suboptimal complementary feeding practices contribute to high stunting rates. Fathers influence complementary feeding practices, and effective strategies are needed to engage them. The objectives of this research were to examine the acceptability and feasibility of (1) tailored complementary feeding recommendations and (2) engaging fathers in complementary feeding. We conducted trials of improved practices with 50 mothers and 40 fathers with children 6–18 months. At visit 1, mothers reported current feeding practices and fathers participated in focus group discussions. At visit 2, mothers and fathers received individual, tailored counselling and chose new practices to try. After 2 weeks, at visit 3, parents were interviewed individually about their experiences. Interview transcripts were analysed thematically. The most frequent feeding issues at visit 1 were the need to thicken porridge, increase dietary diversity, replace sugary snacks and drinks and feed responsively. After counselling, most mothers agreed to try practices to improve diets and fathers agreed to provide informational and instrumental support for complementary feeding, but few agreed to try feeding the child. At follow‐up, mothers reported improved child feeding and confirmed fathers' reports of increased involvement. Most fathers purchased or provided funds for recommended foods; some helped with domestic tasks or fed children. Many participants reported improved spousal communication and cooperation. Families were able to practice recommendations to feed family foods, but high food costs and seasonal unavailability were challenges. It was feasible and acceptable to engage fathers in complementary feeding, but additional strategies are needed to address economic and environmental barriers.